O significado de cuidar em enfermagem nas unidades críticas - Silva, Regina Célia Carvalho da (2003)
The nursing in the criticai units developed itself tlirough an empire of technology in an assistance modcl based on attendance protocols, gravity scores, prognoses scalc, with the professionals leading performance to a characteristically technical. This study aimed at revealing the meaning of care to nurses who work in criticai units, based on Watson’s presuppositions; identifying the coherence between the meaning expressed in discourse and the care practice given by the nurses and detecting the interfaces between the care actions, considering the socio-political-cultural context and the dimensions involved in this care. Inspired in Jean Watson’s human care theory, we chose a qualitative methodology. The subjects of the research werc 12 (twelve) nurses, who all worked in criticai units for adult patients’ treatment. Nine of them are fcmales and three are males and they have been graduated for about 8 years and in the 39-years-old age group. The data were collected by the researcher, who uscd the participative observation and semi-structurcd interview. For the data analysis, one used the contenfs analysis method, according to Bardin (1977), centered in the categorical analysis technique. The data show that the care given by nurses in criticai units is centered on expressive and instrumental dimensions. These were organized in four categories, whicli are: the meeting between the caregiver and the being cared; the care in criticai units; factors that influence and determine the care in criticai units and the care person in criticai units. Starting from the confrontation between the obtained material tlirough the interviews and what has been observed, one noticed a relative equilibrium between the expressive dimension of care, strongly emphasized in nurses’ discourses, and the instrumental dimension, observed according the nurses’ way of caring, strongly influenced and determined by factors of personal, institutional and socio-cultural nature.